Corynebacterium Cell Factory Design and Culture Process Optimization for Muconic Acid Biosynthesis. Issue 1 (December 2018) - Lee, Han-Na; Shin, Woo-Shik; Seo, Seung-Yeul; Choi, Si-Sun; Song, Ji-soo; Kim, Ji-yeon; Park, Ji-Hoon; Lee, Dohoon; Kim, Sang; Lee, Sang; Chun, Gie-Taek; Kim, Eung-Soo
Abstract Muconic acid (MA) is a valuable compound for adipic acid production, which is a precursor for the synthesis of various polymers such as plastics, coatings, and nylons. Although MA biosynthesis has been previously reported in several bacteria, the engineered strains were not satisfactory owing to low MA titers. Here, we generated an engineeredCorynebacterium cell factory to produce a high titer of MA through 3-dehydroshikimate (DHS) conversion to MA, with heterologous expression of foreign protocatechuate (PCA) decarboxylase genes. To accumulate key intermediates in the MA biosynthetic pathway, aroE (shikimate dehydrogenase gene), pcaG/H (PCA dioxygenase alpha/beta subunit genes) andcatB (chloromuconate cycloisomerase gene) were disrupted. To accomplish the conversion of PCA to catechol (CA), a step that is absent inCorynebacterium, a codon-optimized heterologous PCA decarboxylase gene was expressed as a single operon under the strong promoter in aaroE-pcaG/H-catB triple knock-outCorynebacterium strain. This redesignedCorynebacterium, grown in an optimized medium, produced about 38 g/L MA and 54 g/L MA in 7-L and 50-L fed-batch fermentations, respectively. These results show highest levels of MA production demonstrated inCorynebacterium, suggesting that the rational cell factory design of MA biosynthesis could be an alternative way to complement petrochemical-based chemical processes.